Modeling the Wake of the Marquesas Archipelago. Issue 2 (12th February 2018) - Raapoto, H.; Martinez, E.; Petrenko, A.; Doglioli, A. M.; Maes, C.
Abstract: In this study, a high‐resolution (∼2.5 km) numerical model was set up to investigate the fine‐scale activity within the region of the Marquesas archipelago. This has never been performed before. The robustness of the model results is assessed by comparison with remote sensing and in situ observations. Our results highlight regions of warm waters leeward of the different islands with high eddy kinetic energy ( EKE ) on their sides. The analysis of energy conversion terms reveals contributions to EKE variability by wind, baroclinic, and barotropic instabilities. The use of a geometry‐based eddy detection algorithm reveals the generation of cyclonic and anticyclonic eddies in the wake of the largest islands, with both an inshore and offshore effect. Maximum eddy activity occurs in austral winter following the seasonality of both wind stress and EKE intensity. Most eddies have a radius between 20 and 30 km and are generally cyclonic rather than anticyclonic. Significant vertical velocities are observed in the proximity of the islands, associated with topographically induced flow separation. Eddy trapping inshore waters are advected offshore in the wake of the islands. The overall influence of these fine‐scale dynamics could explain the strong biological enhancement of the archipelago. Key Points: Characterizing the eddy activity in the island wake of the Marquesas archipelago using high‐resolution ocean model Revealing the importance of the fine‐scale dynamics within the Island Mass Effect